A STUDY ON COOPERATIVE BANKS IN INDIA WITH SPECIAL REFERENCE TO MARKETING STRATEGIES - Jyothi Nethala, Dr. Vijaya; .I.Pathan, Mr. Firozkhan; Sekhar, Mr. S. Chandra (The journal of contemporary issues in business and government, 2022)
This research looks at the marketing and operations practises of rural banks in India's When used in this context, "marketing strategy" refers to any set of actions taken with the intention of increasing demand for a certain product or service. In light of the increased competitiveness in the banking industry, the use of this term has become widespread. Banks, including rural banks, need to employ effective marketing strategies in their operations to please clients in a first-class way in today's fiercely competitive marketplace and rapidly evolving client desires and requirements within the business landscape. Consumers' shifting tastes and preferences in the modern economy have driven banks both small and large to adapt in order to stay competitive and retain their clientele. Inevitably, this will raise the bar for service across the sector, which in turn will stimulate growth in the economy. To stay ahead of the competition, banks need to develop and implement strategies that provide them a distinct advantage. Providing excellent customer service is a crucial component in maintaining a competitive edge. The study's overarching purpose was to learn more about the methods Rural Bank uses in its marketing efforts to win new clients and keep existing ones happy. The information used for the study comes from both primary and secondary sources related to rural banking.